Assessing quality of life and welfare of donkeys in the UK. Issue 6 (12th July 2018) - Thiemann, Alex; Fernandez, Elena Barrio; Rickards, Karen; Harrison, Anna
Abstract : The role of donkeys in the UK and Europe has changed over the past 40 years, and is still changing – these equids are primarily used as companions, but also for tourism, therapy and increasingly for milk production. When it comes to the end of their lives and issues surrounding equine end‐of‐life care, a recent study highlighted that many donkey owners rely on their vet to provide them with information on quality of life (QOL) assessment, geriatric care and euthanasia planning. This article aims to assist veterinary surgeons in assessing donkey welfare and helping owners decide how to improve QOL or whether an end‐point has been reached and euthanasia is indicated.